Labor Productivity and Employment Gaps in Sub-Saharan Africa - McCullough, Ellen B. (World Bank, Washington, DC, 2015)
Drawing on a new set of nationally representative, internationally comparable household surveys, this paper provides an overview of key features of structural transformation—labor allocation and labor productivity—in four African economies. New, micro-based measures of sector labor allocation and cross-sector productivity differentials describe the incentives households face when allocating their labor. These measures are similar to national accounts-based measures that are typically used to characterize structural changes in African economies. However, because agricultural workers supply far fewer hours of labor per year than do workers in other sectors, productivity gaps disappear almost entirely when expressed on a per-hour basis. What look like large productivity gaps in national accounts data could really be employment gaps, calling into question the prospective gains that laborers can achieve through structural transformation. These employment gaps, along with the strong linkages observed between rural non-farm activities and primary agricultural production, highlight agricultures continued relevance to structural change in Sub-Saharan Africa.